2002
DOI: 10.1093/ptj/82.7.692
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Ethics Knowledge in Physical Therapy (1970–2000)

Abstract: Background and Purpose. Purtilo, Guccione, and others have noted that increased clinical autonomy for physical therapists presents more complex ethical dilemmas. The body of literature examining physical therapy ethics, however, is relatively small and has not been analyzed. The primary purposes of this research were: (1) to use multiple perspectives to describe and analyze literature examining ethics in physical therapy from 1970 to 2000, (2) to develop a model to describe the evolution of knowledge of ethics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 79 publications
(14 reference statements)
0
27
0
6
Order By: Relevance
“…The ethical dilemmas identified by our participants are not unique to the speech pathology profession. Allied health, medical and nursing professions are confronted by the challenges of an evolving healthcare system (Barnitt 1998, Purtilo 2000, Shinn 2004, Swisher 2002). Hence, these ethical challenges present healthcare professionals with new opportunities for collaboration, education and research in applying, maintaining and refining codes of ethics relevant for contemporary practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethical dilemmas identified by our participants are not unique to the speech pathology profession. Allied health, medical and nursing professions are confronted by the challenges of an evolving healthcare system (Barnitt 1998, Purtilo 2000, Shinn 2004, Swisher 2002). Hence, these ethical challenges present healthcare professionals with new opportunities for collaboration, education and research in applying, maintaining and refining codes of ethics relevant for contemporary practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that health professionals are confronted by a range of ethical dilemmas in the workplace (Barnitt 1998, Swisher 2002). These dilemmas included managing unethical behaviour by colleagues, clients disagreeing with intervention approaches, difficulties assigning treatment priorities, inadequate supervision and training, and external constraints on clinical decision‐making (Buie 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the medical research field, studies on the concept of patient involvement are still scarce in physical therapy literature. The opportunities to use SDM in healthcare have been previously described in ethicsbased studies [18]- [22], and the current level of SDM use in physical therapy was recently investigated in an observational study performed in thirteen autonomous physical therapy settings at the Flemish part of Belgium [23]. However, our observational study [22], as well as various studies in the field of general practice [23]- [26], reported that SDM was rarely implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 94%
“…Em relação ao direito, o Estado precisou intervir nas relações para melhor defini-lo, a necessidade era e é de um agente imparcial para mediar os conflitos das relações humanas, criando-se então os códigos, leis e normas (7,9). No que se refere às categorias profissionais, surgiu a necessidade de estabelecer regras com a finalidade de instituir os princípios ético-morais pelos quais os profissionais poderiam se guiar, regulando, assim, sua atuação.…”
Section: Fundamentação Teóricaunclassified